Commentary on Bedside terminals and quality of nursing documentation [original article by Marr P et al appears in COMP NURS 1993;11(4):176-82]. - Nevidjon BM (AONE's Leadership Prospectives)
Problem: To evaluate the relationship between completeness and timeliness of nursing documentation when using bedside terminals versus centrally located terminals. Subject: Four documentation aspects -- medication administration, daily charting, physical assessment, admission nursing notes -- studied from patient records on two med units with similar patient populations, acuity, and RN staffing patterns. Method: In a before/after, parallel, control-group design one unit was designated as the experimental unit. In the before phase, the authors randomly selected 45 patient days to collect data on the four documentation aspects. Both units had computer terminals located in the central nurses station. In the after phase, the process was repeated but the experimental unit also had bedside computer terminals. Findings: Contrary to expectations, having terminals at the patient's bedside demonstrated no significant benefit in quality of documentation. Conclusion: In this first of a three-part investigation, results have made the authors question why, given a choice of locations, nurses choose not to use bedside terminals.